Cardiac Mineralocorticoid Receptor and the Na⁺/H⁺ Exchanger: Spilling the Beans - Ennis, Irene Lucía (2021)
Current evidence reveals that cardiac mineralocorticoid receptor (MR) activation following myocardial stretch plays an important physiological role in adapting developed force to sudden changes in hemodynamic conditions. Its underlying mechanism involves a previously unknown nongenomic effect of the MR that triggers redox-mediated Na⁺/H⁺ exchanger (NHE1) activation, intracellular Na⁺ accumulation, and a consequent increase in Ca²⁺ transient amplitude through reverse Na⁺/Ca²⁺ exchange. However, clinical evidence assigns a detrimental role to MR activation in the pathogenesis of severe cardiac diseases such as congestive heart failure. This mini review is meant to present and briefly discuss some recent discoveries about locally triggered cardiac MR signals with the objective of shedding some light on its physiological but potentially pathological consequences in the heart.